Advancing carbon sequestration and nutrient management in the South African dairy industry for sustainable growth - Reinecke, Riana; Blignaut, James N.; Meissner, Heinz H.; Swanepoel, Pieter A. (Frontiers in Sustainable Food Systems, 2024)
The dairy industry in South Africa is currently grappling with significant challenges, including escalating costs and diminishing profit margins. However, these difficulties also create a pivotal opportunity for the sector to embrace sustainable practices that not only enhance environmental stewardship but also encourage economic resilience. A crucial step in this transition is to dispel prevalent misconceptions about the industry’s environmental footprint and to highlight its positive contributions to sustainable agricultural practices. Farmers are encouraged to adopt innovative strategies that enhance soil health and reduce their ecological impact. This review focuses on essential factors influencing nutrient management and the processes that contribute to soil carbon enhancement. Effective management is crucial for the sustainability of pasture-based dairy systems, as herbage biomass significantly influences nutrient cycling and soil organic matter accumulation. For instance, well-managed pastures with high biomass can efficiently recycle nutrients from manure, enhancing plant growth. This process contributes to soil organic carbon buildup, which aids in carbon sequestration. In contrast, poor nutrient management can lead to nutrient imbalances and lower herbage production, reducing carbon storage potential. Moreover, the movement of nutrients below the surface is a critical pathway for enhancing soil health and promoting ecological balance. By implementing sustainable practices and refining nutrient stewardship strategies, pasture-based dairy farmers can significantly advance their sustainability goals. This includes recognizing the broader implications of soil health on farm productivity and environmental resilience, as well as the potential for improved biodiversity.